2017
DOI: 10.1088/1674-1056/26/1/016402
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous physics and materials: Secondary relaxation and dynamic heterogeneity in metallic glasses: A brief review

Abstract: / 24Understanding mechanical relaxation, such as primary ( and secondary (relaxation, is key to unravel the intertwined relation between the atomic dynamics and non-equilibrium thermodynamics in metallic glasses. At a fundamental level, relaxation, plastic deformation, glass transition and crystallization of metallic glasses are intimately linked to each other, which can be related to atomic packing, inter-atomic diffusion and cooperative atom movement. Conceptually,  relaxation is usually associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 111 publications
2
24
0
Order By: Relevance
“…The presence of the loss peak, referred to as γ‐relaxation, in all these different alloys suggests a general phenomenon of a fast relaxation mechanism at low temperatures, which is in agreement with subsequent studies . The activation energy of this process is of the order of 0.2–0.3 eV, which offsets it distinctly from α‐ and β‐relaxation that typically have higher activation barriers of several electron volts and 0.6–1.5 eV, respectively.…”
Section: Tuning Structure Homogeneously Via Thermal and Mechanical Prsupporting
confidence: 88%
“…The presence of the loss peak, referred to as γ‐relaxation, in all these different alloys suggests a general phenomenon of a fast relaxation mechanism at low temperatures, which is in agreement with subsequent studies . The activation energy of this process is of the order of 0.2–0.3 eV, which offsets it distinctly from α‐ and β‐relaxation that typically have higher activation barriers of several electron volts and 0.6–1.5 eV, respectively.…”
Section: Tuning Structure Homogeneously Via Thermal and Mechanical Prsupporting
confidence: 88%
“…The β relaxation is an intrinsic and fundamental characteristic in metallic glasses (MGs), which is important to understand many crucial issues in material sciences and glassy physics, such as mechanical properties, diffusion behavior, crystallization process and glass transition [1][2][3][4][5][6][7][8]. Consequently, an in-depth understanding of the structural origin of the β relaxation is deemed necessary for both scientific researches and practical applications of MGs.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that the relaxation happens in almost all the timescales which can be roughly separated into three types when it is close to glass transition temperature (Tg) [2,3]: (1) The primary one, named α-relaxation with the typical timescale >10 -3 s, is associated with structural relaxation and play the main role in glass transition; (2) the secondary relaxation with the timescale of 10 -8~1 0 -3 s, which is often called (slow) β relaxation, is related to localized atomic motion though a mechanism that is still vague; (3) and the third relaxation with the timescale of 10 -8~1 0 -12 s, usually called fast β relaxation, could be related to the rattling motion of caged particles [4]. At present, lots of efforts have been devoted to the understanding of β relaxation [3,[5][6][7][8][9][10][11][12] because it helps disclose the nature of glass transition [10] and adjust the properties of glass [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the rotational diffusion about the C2v axis in poly(methyl methacrylate) (PMMA) does not induce the change of dielectric properties; therefore, only mechanical approach can reveal the corresponding relaxation process [9]. For metallic glasses, the internal friction associated with β relaxation can only be observed through mechanical means [11] because there is no re-orientation of atomic dipoles. Johari [24] suggested that a mechanical β relaxation is essentially due to the translational motion of atoms in metallic and other glasses, which is consistent with the conception of "islands of mobility" proposed by Johari and Goldstein [16].…”
Section: Introductionmentioning
confidence: 99%